Overcoming Preexisting Humoral Immunity to AAV Using Capsid Decoys - Mingozzi, Federico (2013)
Adeno-associated virus (AAV) vectors delivered through the systemic circulation successfully transduce various target tissues in animal models. However, similar attempts in humans have been hampered by the high prevalence of neutralizing antibodies to AAV, which completely block vector transduction. We show in both mouse and nonhuman primate models that addition of empty capsid to the final vector formulation can, in a dose-dependent manner, adsorb these antibodies, even at high titers, thus overcoming their inhibitory effect. To further enhance the safety of the approach, we mutated the receptor binding site of AAV2 to generate an empty capsid mutant that can adsorb antibodies but cannot enter a target cell. Our work suggests that optimizing the ratio of full/empty capsids in the final formulation of vector, based on a patient's anti-AAV titers, will maximize the efficacy of gene transfer after systemic vector delivery.